Innovative technologies in the educational process - Igor Vasilievich Нevko; Iryna Bogdanivna Lutsyk (Kazimierz Wielki University, 2019)
Among the priority directions of the state policy on the development of higher education in the context of European integration of Ukraine are identified the problem of continuous improvement of the quality of education, modernization of its content and forms of organization of the educational process; introduction of educational innovations and information technologies. Improving the quality of future teacher training aimed at implementing the provisions of the Bologna Declaration. The article presents an assessment of the effectiveness of implementing educational innovations and information technologies to improve the quality of the education system as a whole. Particular attention is paid to the use of innovative and information technologies to train future teachers.